Settlements, landscape and palaeoclimate dynamics on the Ižica floodplain of the Ljubljana Marshes - Budja, Mihael (Documenta Praehistorica, 2008)
In this paper we present the results of the radiocarbon dating of organic sediments from palaeochannels we have mapped by LiDAR (Light Detection and Ranging) imagery on the Ižica floodplain. We point out that the palaeochannels and the settlement structures at Maharski prekop site are contemporaneous. We hypothesise that the episodes in past river behaviour on the Ljubljana Marshes correspond with climate anomalies in European palaeoclimate records in the Holocene.
Keywords: Ljubljana Marshes; Ljubljansko barje; prazgodovina; poselitev; naselja; klimatske spremembe; paleoklimatologija; datiranje; neolitik